A2.33 Haplotype TTTT in the BAFF gene is associated with idiopathic inflammatory myopathies in HLA-DRB1*03 negative patients. (13th February 2015) - Kryštůfková, O; Svitálková, T; Remáková, M; Pleštilová, L; Mann, H; Novota, P; Vencovský, J
Abstract : Background and objectives: B-cell activating factor of the TNF family (BAFF) plays a role in (auto)antibody production. Patients with idiopathic inflammatory myopathies (IIMs or myositis) have elevated levels of BAFF in the serum which associate with disease activity. We have previously found an association between TTTT haplotype from the four single nucleotide polymorphisms (SNPs) in the promoter region of BAFF gene (rs9514827, rs3759467, rs1041569 and rs9514828) with presence of myositis in our cohort of IIM patients. The HLA-DRB1*03 allele is a well-known genetic risk factor for myositis in Caucasians. In this study we have analysed the possible interference of HLA-DRB1*03 allele with the presence of the particular SNPs of BAFF gene in patients with myositis. Materials and methods: The SNPs (rs9514827, rs3759467, rs1041569 and rs9514828) were analysed by direct DNA sequencing in a cohort of 311 patients with myositis (age 5–80 years, females 74%) and in 113 healthy controls (age 18–79 years, females 69%). The HLA-DRB1 genotyping with PCR using sequence-specific oligonucleotide and sequence based typing technique was available in the subgroups of 297 patients and 103 controls. The χ 2 or Fisher tests for analysis of allelic, haplotype and genotype associations with Bonferroni's correction were used. Results: The four BAFF SNPs were in strong linkage disequilibrium and formed four common haplotypes (TTAC, CTAT, TCAC, TTTT) in both IIM patients and controls, compatible with already reported results. A significantly higher frequency of the TTTT haplotype was present in myositis patients compared to healthy controls (16% vs. 10%; OR = 1.65, 95% CI = 1.03–2.65; p < 0.05). There were no significant differences between patients and controls in the frequencies of alleles and genotypes. 162 IIM patients (55%) and 87 healthy controls (84%) were HLA-DRB1*03 negative and a significant association of the TTTT haplotype in IIM patients was confirmed by a higher frequency (19%) compared to controls (11.5%; OR = 1.79, 95% CI = 1.04–3.07; p < 0.05) within the DRB1*03 negative cohorts. The trend for lower frequency of -2701A allele and AA genotype (rs1041569) in myositis was also found within the HLA-DRB1*03 negative cohort, with IIM patients having a significantly lower proportion of AA genotype compared to controls (62% vs. 77%; OR = 0.48, CI = 0.27–0.87; p < 0.05). Conclusions: An association of the TTTT haplotype with myositis and a lower frequency of -2701 A allele and AA genotype in patients with IIM are independent from the presence of HLA-DRB1*03 risk allele. Acknowledgements: IGA-MZ CR NT/12438–4, IMI-funded project BeTheCure, 115142-2